THE RELATIONSHIP BETWEEN FEAR OF COVID-19 AND ADHERENCE FOR PEOPLE WITH END STAGE RENAL DISEASES WITH HEMODIALYSIS - Nining Puji Astuti; Arief Shofyan Baidhowy; Erlangga Galih Zulva Nugroho (Jurnal Ilmu Keperawatan Medikal Bedah, 2022)
Patients with End-Stage Renal Disease (ESRD) are highly vulnerable with the multiple comorbidities that make them susceptible to adverse outcomes with COVID-19. Over 2 million people worldwide receive maintenance hemodialysis (HD) at outpatient centers. In Indonesia, people have to come to dialysis centre at hospital for maintenance dialysis although in pandemic. Governments have been trying to fight the outbreak, by enacting various restrictions to maintain social distancing and effectively preventing the spread of infection among HD centre, healthcare personnel, and patients is essential to ensure the continued delivery of dialysis to ESRD patients but this condition affect in mental health people with hemodialysis such as fear of covid-19. The present study aimed to understand the relationship between fear of covid-19 and adherence people with hemodialysis to maintaining hemodialysis at hospital. The study group of the research consisted of 60 patients with hemodialysis were selected by the purposive sampling method. The research method is the correlational survey model. Data was obtained using the Demographic Information Form, fear of covid-19 scale and The End Stage Renal Disease Adherence Questionnaire (ESRD-AQ). Group comparison analysis revealed that women experienced higher levels of fear of the coronavirus. While those with postgraduate education reported significantly lower levels of fear of the coronavirus than those with other education levels. Fear of the coronavirus did not differ according to the age range, income level, and marital status of the participants. According to the results of the correlation analysis, a positive correlation between the fear of coronavirus and adherence people with hemodialysis to take medication at hospital was found.